The Ambiguities of Working with Third-Party Recruiters: Essential Dilemmas - Reisberg, Liz; Altbach, Philip (International Higher Education, 2011)
The use of agents and recruiters to enroll international students in universities in United States and other major receiving countries is growing. There are problems with this practiceincluding ethical questions. The authors advocate using other ways of informing potential international students of opportunities for study abroad.